Financial Technology Utilization and Budgeting Discipline Affecting Sustainability Performance through Financial Inclusion in Indonesian Handicraft MSMEs - Yuni Utami; Yanti Puji Astutie (ICON Publisher, 2026)
This study investigates the influence of financial technology utilization and budgeting discipline on sustainability performance through financial inclusion in Indonesian handicraft MSMEs. Using a quantitative approach, data were collected from 212 MSME owners and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that financial technology utilization and budgeting discipline significantly enhance financial inclusion. Furthermore, both variables have direct positive effects on sustainability performance. Financial inclusion also demonstrates a significant positive impact on sustainability performance, confirming its role as a mediating mechanism. These findings suggest that the integration of digital financial services and structured financial management practices plays a crucial role in improving MSME sustainability. The study contributes to the literature by extending Financial Inclusion Theory through the incorporation of technological and behavioral factors. Practically, the results provide insights for policymakers and practitioners in promoting financial inclusion and sustainable business practices. However, the study is limited by its cross-sectional design and sample scope. Future research is recommended to explore additional variables and longitudinal data to enhance generalizability. Overall, this study highlights the importance of financial access and management in achieving sustainable MSME performance.